Assistance of Integrated Thematic Tourism Village Pioneers in Pematang Johar Village, Labuhan Deli District - Kamtini, Kamtini; Mailani, Elvi; Purnomo, Try Wahyu (Journal of Community Research and Service, 2023)
This Community Partnership Program aims to provide alternative solutions to the problems faced by partners, including: (1) lack of information and publications about tourism potential that can be exposed in Pematang Johar Village, (2) the absence of integrated media that can integrate all village tourism potential, (3) there is no location that is used as a tourist literacy center, (4) educational facilities are not optimal to support tourist interest in visiting Pematang Johar Village Several series of activities in this PKM program are: (1) preparation (2) implementation of activities, (3 ) monitoring and evaluation, (4) follow-up. The method used. Based on the problems and activity plans, there are several activities carried out as solutions to partner problems, including: (1) integrated tourism concept assistance referring to the development of thematic villages, (2) making integrative tourism pocket books, (3) creating tourist literacy rooms, (4) designing a plank map of Pematang Johar tourist destinations. Through the activities produced by the output of integrative tourist destination pocket books, literacy rooms, x-banners of tourist information centers and plank maps of tourist destinations in Pematang Johar. The implementation of these activities is expected to optimize the management of village tourism carried out by the Tourism Awareness Group so that it can become an integrative thematic tourism area that is worthy of education in Pematang Johar Village, Kec. Labuhan Deli, Kab. Deli Serdang